Interpretive Reception of the Qur’an in the Film Bid’ah: Religious Manipulation and the Construction of Truth in Michel Foucault’s Discourse Analysis - Musolli Musolli; Aida Nuriyah; Salih Abdulrahman Alsounusi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2026)
The representation of Islam in contemporary media often intersects with issues of religious authority, symbolic power, and the misuse of sacred texts. The film Bid’ah provided a critical depiction of religious manipulation through the cult of leadership, blind obedience, ritual deviation, and the misuse of Qur’anic verses to legitimize spiritual domination. This study aimed to examine the interpretive reception of the Qur’an in Bid’ah and to analyze how religious manipulation was constructed through discourse and power relations. This research employed a descriptive qualitative method by combining Michel Foucault’s discourse analysis with Qur’anic reception studies. The data were collected from selected scenes, dialogues, and narratives in the film and were analyzed thematically by relating them to relevant Qur’anic verses. The findings showed that religious manipulation in Bid’ah operated through the production of truth, the normalization of obedience, bodily discipline, and the symbolic authority of a sect leader. Qur’anic verses were represented not merely as sacred references, but also as contested texts that could be interpreted, distorted, or resisted within power relations. This study concluded that film Bid’ah offers an important media representation of how Qur’anic discourse can be misused to sustain religious authority while also affirming the Qur’anic principles of monotheism, critical reasoning, and ethical resistance.